A synthesis of dioctanoyl phosphatidylinositol - Elliott, T; Nemeth, J; Swain, SA; Conway, S (2009)
A synthesis of the naturally occurring enantiomer of phosphatidylinositol is reported. A resolution strategy, using camphor as a chiral auxiliary is employed to obtain the desired, enantiomerically pure, inositol derivative. Dioctanoyl lipid chains are appended to the molecule, which are shorter than the naturally occurring lipid chains, providing the molecule with enhanced water solubility. © 2009 Elsevier Ltd. All rights reserved.